2017
DOI: 10.1177/1350650117739200
|View full text |Cite
|
Sign up to set email alerts
|

Load and stiffness of a planar ferrofluid pocket bearing

Abstract: A ferrofluid pocket bearings is a type of hydrostatic bearing that uses a ferrofluid seal to encapsulate a pocket of air to carry a load. Their properties, combining a high stiffness with low (viscous) friction and absence of stick-slip, make them interesting for applications that require fast and high precision positioning. Knowledge on the exact performance of these types of bearings is up to now not available. This article presents a method to model the load carrying capacity and normal stiffness characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…With  of P(C, , D) varying from 0 to 2, B doesn't change in magnitude. At the point P(C, 0, D), the magnitude of the displacement vector R o can be given as (14) According to Biot-Savart Law, B o at the point P(C, 0, D) can be given as (15) where B ox , B oy , and B oz are the components of the mag-…”
Section: Calculation Of the Magnetic Field Strength In Magnetic Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…With  of P(C, , D) varying from 0 to 2, B doesn't change in magnitude. At the point P(C, 0, D), the magnitude of the displacement vector R o can be given as (14) According to Biot-Savart Law, B o at the point P(C, 0, D) can be given as (15) where B ox , B oy , and B oz are the components of the mag-…”
Section: Calculation Of the Magnetic Field Strength In Magnetic Fluidmentioning
confidence: 99%
“…Later in the book titled "ferrohydrodynamic", Rosensweig gave a detailed description on the particular magnetic levitation force (selfsuspension buoyancy) by means of magnetic fluid stress tensor [3]. Up to now, this property of magnetic fluid has been exploited in many innovative devices, such as dampers [4][5][6], sensors [7][8][9][10][11], actuators [12][13][14], bearings [15,16], micromechanical system [17][18][19] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of hydrodynamic lubrication with ferrofluids of finite journal bearings using the Jenkins model has been done by Laghrabli et al 25 They analyzed static characteristics of finite journal bearings using two control parameters: magnetic force coefficient and Jenkins viscosity. Lampaert et al 26 studied the load capacity and the stiffness of a ferrofluid pocket bearing. They showed that the load and stiffness of this bearing are in general mainly determined by the sealing capacity of the seal and the pressure of the ferrofluid itself.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of tribo-mechatronics and control has divided the active hydrostatic bearings into three classes. In class one, researchers have tried to use the external magnetic field for controlling viscosity of the magnetic fluid, so that the shaft vibrations could be controlled [20][21][22][23][24]. In the second class, authors tried to control recess pressure, and efforts were made to control the recess pressure through a piezoelectrically activated jet [25,26].…”
Section: Introductionmentioning
confidence: 99%